Medicine, torture, the death penalty and the democratic state: from collaboration to emancipation - Greco, Dirceu B.; Welsh, James (Revista Bioética, 2019)
Abstract Abuses of medicine have taken place over past decades in the context of torture and the death penalty. Serious and totally unacceptable breaches of medical ethics and human rights have occurred in institutions caring for vulnerable people. And yet there is still a need to make visible the whole spectrum of violence and breaches of human rights and to challenge them. This paper discusses a wide range of abuses in which medical professionals may take part whether as witnesses, bystanders or participants. It also addresses changes that are needed to benefit citizens at risk of abuse and to strengthen the ethical practice of medicine. The frequently-used term “empowerment” as applied to populations at risk signals a step in the right direction but usually involves the top-down giving of limited power to people. What oppressed people need is to claim their human rights – to emancipate themselves. Keywords: Bioethics. Ethics. Human rights. Torture. Capital punishment.